Pengaruh Total Asset Turnover Dan Corporate Governance Terhadap Kinerja Keuangan Sebelum Pandemi Dan Saat Pandemi Covid-19 - Almega, Echa Septa; Yuliansyah, Yuliansyah (Goodwood Akuntansi dan Auditing Reviu, 2024)
Purpose: This study aims to determine the simultaneous and partial influence of independent variables, namely institutional ownership and Total Asset Turnover (TATO) on the dependent variable, namely Return On Assets (ROA). Methodology/approach: The population used in this study is the population of processed food sector companies listed on the Indonesia Stock Exchange from 2017 to 2022 totaling 19 companies. Meanwhile, the samples used in this study were 98 samples of processed food companies listed on the Indonesia Stock Exchange in the period 2017 to 2022. The data collection technique in this study used the Purposive sampling method. The data analysis techniques used in this study are Normality Test, Multicollinearity Test, Heteroscedasticity, Autocorrelation Test, Simultaneous Significance Test, Individual Parameter Significance Test, and Coefficient of Determination. Results/findings: Based on the results of this study, it can be concluded that TATO has a positive effect on ROA while SKI has a negative effect on ROA in processed food companies on the IDX for the 2017-2022 period. Limitations: The limitations in this study are that there are only two fundamental factors, namely Total Assets Turnover and Corporate Governance, and the sample used is only processed food industry companies that do not represent all sub-sectors of other companies. Contribution: This research can be used as a literature reference for future research, especially research on Total Assets Turnover and Corporate Governance.